INOVASI PEMBELAJARAN BERBASIS ALAM: ECOPRINT SARANA PENDIDIKAN LINGKUNGAN PADA SISWA SMP NEGERI 9 PAREPARE - Dewi Sulistiawati; Abdul Rahman; Rizqy Rizqy; Muhammad Azhar Ramdani Suardi (Mediasi: Jurnal Pengabdian Masyarakat, 2025)
The ecoprint technique is a form of textile art that uses natural materials, such as leaves and flowers, to print patterns and colors on fabric or paper. This process involves direct contact between plants and textile materials, with the aim of creating unique and environmentally friendly patterns. This service activity reviews ecoprint training activities carried out at UPTD SMP Negeri 9 Parepare on 28 November 2024. This activity involved 21 students who practiced ecoprint techniques through exploratory steps, such as preparing tools and materials, selecting plants, arranging media, pounding processes, and drying the work. The results of the activity showed that students were very enthusiastic about this technical training and succeeded in producing attractive and environmentally friendly ecoprint works. Apart from developing artistic skills, this activity also aims to increase students' awareness of the importance of maintaining environmental sustainability.